Hubungan Waktu Penggunaan Komputer Terhadap Kejadian Computer Vision Syndrome Pada Mahasiswa Fakultas Ilmu Komputer Universitas Muhammadiyah Riau - isnaniar, Isnaniar; Norlita, Wiwik; Afrizen, Pingki (As-Shiha: Jurnal Kesehatan, 2021)
The use of computers can cause a health complaint called Computer Vision Syndrome (CVS). This syndrome can be influenced by various individual and computer risk factors. The purpose of this study was to determine the relationship between computer use time and Computer Vision Syndrome in students of the Faculty of Computer Science, University of Muhammadiyah Riau. Methods: The design of this study is a sampling technique accidental sampling, amounting to 83 respondents. Data collection using a questionnaire. Results: research that was conducted on 18-20 November 2018 obtained results regarding the overall length / duration of work of respondents in front of a computer ≥2 hours, namely as many as 83 respondents (100%), most of the respondents had a history of using computers for 8 years, namely 26 respondents (31.3%), data on respondents affected by CVS (≥ 3 complaints) after using computers were 47 (56.6%) respondents, while respondents who were not affected by CVS (≥ 3 complaints) after using computers were 36 (43.4%) respondents. The CVS complaints experienced were eyes tired and tense 53 (63.9%), dry irritated eyes 27 (32.5%), blurred vision 36 (43.4%), headaches 47 (56.6%), severe eyes 42 (50.6%) 34 (41%) watery eyes and difficulty focusing 36 (43.45%) Keywords: Old Computer Usage Time Working at Computer, Computer Vision Syndrome